2011
DOI: 10.1002/lt.22232
|View full text |Cite
|
Sign up to set email alerts
|

CD28 expression by peripheral blood lymphocytes as a potential predictor of the development of de novo malignancies in long-term survivors after liver transplantation

Abstract: At present, no method is available for accurately monitoring the degree of immunosuppression induced by antirejection therapies. The aim of this study was to determine whether CD28 and CD38 expression by peripheral blood mononuclear cells could be useful in predicting the development of de novo malignancies after liver transplantation. Flow cytometry analysis was used to measure the expression of CD28 and CD38 by peripheral blood lymphocytes in 134 stable, long-term survivors of liver transplantation. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
(28 reference statements)
0
8
0
1
Order By: Relevance
“…Wieland and Shipkova, Lymphocyte surface molecules 7 transplantation is very limited and, as mentioned above, the patient cohorts that are included are small. Table 1 summarizes the studies and markers that were used in clinical trials that aimed at outcome measurements.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 2 more Smart Citations
“…Wieland and Shipkova, Lymphocyte surface molecules 7 transplantation is very limited and, as mentioned above, the patient cohorts that are included are small. Table 1 summarizes the studies and markers that were used in clinical trials that aimed at outcome measurements.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…An interesting concept is to use donor-specific peptides that are presented to the recipient T cells semi-directly through antigen presenting cells. For the assessment of CD28, CD26 and CD95 (FasL) on the cell surface of T cells, normally no ex vivo stimulation step is required [7][8][9]. The specific and non-specific can be anticipated that standardization of methods for measuring less well characterized biological macro molecules such as the surface antigens is a very challenging task.…”
Section: Analytical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the complicated cell function assays using ex vivo stimulation, the measurement of CD26 on CD3 cells directly in whole blood seems to allow for a statement about the degree of activation of the T-cells in vivo. Boleslawski et al report, in connection with liver transplantation, that CD28 on CD8 cells can be associated with both rejections in the early phase after transplantation (many CD28/CD8 cells) and tumor diseases over the long term (few CD28/ CD8 cells) [39,40] .…”
Section: T-cell Surface Markersmentioning
confidence: 99%
“…Boleslawski et al reported an association between a decreased level of CD28 expression on CD8 þ cells and malignancies in long-term liver transplant patients, as well as an association between increased expression and rejection [84,85]. So far, no standardization of assay protocols has been achieved and no sound data from larger clinical trials have been published.…”
Section: T Cell Activation Surface Markersmentioning
confidence: 99%